Kepatuhan Penderita Diabetes Mellitus di Apotik Ubaya Berdasarkan Tinkgkat Kepatuhan dan Motivasi - Kristianto, Franciscus Cahyo; Susilo, Astrid Pratidina (Jurnal Farmasi Indonesia, 2015)
Adherence is one of the important things for diabetic patients to control their blood glucose level and preventing for complications in the future. There are two major factors that influence the adherence, patientâ??s knowledge and motivation. Design of this study was sequential mixed method. Thirty type 2 diabetes mellitus patients were recruited based on patient medication record prepared by the community pharmacist. At the first stage, subjects were asked to answer four validated questionnaires that related with level of knowledge (health literacy and medication knowledge) and motivation (readiness to change and social support). At the second stage, they were interviewed based on their response to readiness to change questionnaire. All data collected were then analysed descriptively and qualitatively. From knowledge aspects, there were 93% of patients has high level of health literacy and 87% has high medication knowledge. From motivation aspects, there were 70% has changed and maintained their adherence, 20% were still prepare to change (preparation) and 10% were not ready to change (contemplation). Need for social supports were very high (97%) within the diabetic patients. Most of the subjects (80%) have high level of knowledge and motivation. There were 17% who has variable knowledge and motivation and only 3% who has low level of knowledge and motivation.